THE EFFECT OF TOTAL QUALITY MANAGEMENT ON EMPLOYEE PERFORMANCE WITH COMPENSATION AS MODERATION VARIABLE - Aurora Angela; Sari Endah Purnama; Oktavianti Oktavianti (Universitas Serang Raya, 2020)
The purpose of this study is to find out the effect of Total Quality Management (TQM) on employee work performance, mainly when moderated by compensation variables. This research is at commercial banks in Bandung, along with their surroundings. The respondents of the particular study are the employees of the commercial banks. The technique to test the hypothesis is called the Simple Linear Regression Analysis. It is set to determine the effect of TQM on the employee work performance and Moderated Regression Analysis (MRA) to assess the impact of TQM on the employee work performance in times of moderation utilizing the compensation variables. The result of this study is that the application of TQM affects employee work performance. Furthermore, being a moderating variable, compensation has a positive influence on the relationship of TQM with employee work performance. Keywords: Total Quality Management (TQM), Compensation, Employee work performance